Enhancing Relationality through Poetic Engagement with PhoneMe: Transmodal Contexts and Interpretive Agency - Ahn, Claire; Balyasnikova, Natalia; Horst, Rachel; James, Kedrick; Morales, Esteban; Takeda, Yuya; Yung, Effiam (Language and Literacy / Langue et littératie, 2023)
This article explores the role of literary user preference and experience of contextualizing information in the interpretive responses to poems on PhoneMe, a social media web-platform and mobile app for place-based spoken word poetry. 137 education students in three Canadian universities participated by completing a survey that asked them to choose one of three stylistically distinct poems and subsequently introduced multimodal contextual information about the poet and location inspiring the poem. Findings indicate a productive tension between the reader/user’s interpretive agency with typographic text and the increasing relationality imposed by indexical, transmodal information, thus helping to update Reader Response theory.